Effect of Peri-Implant Disease on Adropin Levels: A Cross-Sectional Pilot Study - Gündoğar, Hasan; Özsoy, Buket; Uzunkaya, Meral; Şenyurt, Süleyman Ziya; Erciyas, Kamile (European Journal of Therapeutics, 2023)
Objective: Adropin is a peptide hormone related to the inflammatory process of several systemic diseases. The inflammatory characteristics of peri-implant diseases are known. This study aimed to measure and compare the level of adropin in peri-implant sulcus fluid (PISF) in patients with peri-implant disease. Methods: Overall, 75 individuals were included in this cross-sectional study. Each of the three study groups [healthy (H), peri-implant mucositis (PM), and peri-implantitis (PI)] consisted of 25 patients. During the periodontal examination, periodontal pocket depth (PD), plaque index (PI), and gingival index (GI) scores were recorded, and marginal bone loss (MBL) was measured using ImageJ. PISF samples were collected from dental implants. Adropin level in PISF was analyzed using the enzyme-linked immunosorbent assay (ELISA) technique. All clinical and biochemical parameters were statistically analyzed using SPSS v22. Results: PD, PI, and GI parameters were noted to be significantly higher in the PM and PI groups compared with the H group. PI group showed statistically significant differences related to MBL compared with the other groups (p<0.05). Conclusion: Therefore, adropin may prove to be a useful diagnostic tool in the diagnosis of peri-implant disease. However, further studies are needed to explore the different biochemical parameters in PISF, thereby helping to understand the interaction of adropin with other mediators.